2014
DOI: 10.1534/genetics.114.172544
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by the Engulfment Receptor Draper: A Screen in Drosophila melanogaster Implicates Cytoskeletal Regulators, Jun N-Terminal Kinase, and Yorkie

Abstract: Draper, the Drosophila melanogaster homolog of the Ced-1 protein of Caenorhabditis elegans, is a cell-surface receptor required for the recognition and engulfment of apoptotic cells, glial clearance of axon fragments and dendritic pruning, and salivary gland autophagy. To further elucidate mechanisms of Draper signaling, we screened chromosomal deficiencies to identify loci that dominantly modify the phenotype of overexpression of Draper isoform II (suppressed differentiation of the posterior crossvein in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 133 publications
1
9
0
Order By: Relevance
“…Activation of hep promotes Draper expression, suggesting JNK is required for draper induction during engulfment. Consistent with findings in the ovary, studies in the Drosophila embryonic central nervous system, adult brain, and wing epithelium have shown a requirement for the JNK pathway downstream of Draper ( 27 , 100 , 101 ). Studies in the embryonic central nervous system show that while expression levels of Draper and the bridging molecule Six-microns-under remain the same in glia that have active JNK signaling, hep CA gain of function in draper loss-of-function mutants restores defects in apoptotic clearance ( 101 ).…”
Section: Draper Signals To the Jnk Signaling Pathway In Many supporting
confidence: 70%
See 1 more Smart Citation
“…Activation of hep promotes Draper expression, suggesting JNK is required for draper induction during engulfment. Consistent with findings in the ovary, studies in the Drosophila embryonic central nervous system, adult brain, and wing epithelium have shown a requirement for the JNK pathway downstream of Draper ( 27 , 100 , 101 ). Studies in the embryonic central nervous system show that while expression levels of Draper and the bridging molecule Six-microns-under remain the same in glia that have active JNK signaling, hep CA gain of function in draper loss-of-function mutants restores defects in apoptotic clearance ( 101 ).…”
Section: Draper Signals To the Jnk Signaling Pathway In Many supporting
confidence: 70%
“…In macrophages, JNK is also required for the induction of draper in response to corpses ( 103 ). Surprisingly, overexpression of Draper II, the inhibitory isoform of Draper, results in increased JNK pathway activity in the wing ( 100 ). Taken together, these studies in Drosophila indicate that Draper and JNK regulate each other in multiple cellular contexts.…”
Section: Draper Signals To the Jnk Signaling Pathway In Many mentioning
confidence: 99%
“…We sought to develop an in vivo injury model that would elicit a broader glial response in order to identify differentially expressed genes using a large-scale transcriptional profiling screen. Recent studies revealed that peripheral sensory neurons in the wing undergo a classic Wallerian degeneration program and are cleared by glia in a Draper-dependent manner after axotomy ( Fang et al, 2012 ; Fullard and Baker, 2015 ), suggesting that glial cells throughout the adult fly nervous system use common pathways to sense and respond to degenerating axons. Thus, we turned to the ventral nerve cord (VNC) of the fly with the goal of establishing a more robust in vivo nerve injury assay to query changes in glial gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies of E(Pc) in Drosophila illustrated its critical role in chromatin regulation and we learned that E(Pc) is also involved in genomic imprint maintenance in Drosophila , likely through its role in heterochromatin maintenance (Joanis and Lloyd 2002). E(Pc) has been further highlighted for its important interactions (Table 2) with various genes and proteins involved in apoptosis and chromatin regulation, such as with ISWI (Imitation SWI), His1 (Histone H1), and Polycomb group genes (Ali and Bender 2004; Arancio et al 2010; Fullard and Baker 2015; Kavi et al 2015). As in yeast, E(Pc) is important in the cell cycle in Drosophila , where is it required during development for mitotic exit during the transition to a post-mitotic state (Flegel et al 2016).…”
Section: Comparative Studies Between Model Organisms Promote Functionmentioning
confidence: 99%